(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
In this articie, some antroponyms used in the Xofiz Tanish al-Bukhari’s book “Sharafnomayi Shohiy.” are studied and their assimilation factor is analyzed based on scientific and historical sources.